Which Dimensions of Entrepreneurial Orientation Drive Firm Performance in Hostile Environments? Lessons From the Pandemic Crisis - Marcin Suder (European Management Studies)
Purpose: This study aims to analyze the roles of dimensions of entrepreneurial orientation (EO) – risk- -taking, proactiveness, and innovativeness – within the context of a crisis. Specifically, it evaluates the perspectives of entrepreneurs and managers regarding the impact of these dimensions on firm performance in the hostile environment created by the COVID-19 pandemic. The study adopts a unique perspective, focusing on retrospective assessments by entrepreneurs and managers rather than traditional econometric measurement techniques.